Juridical Review of the Implementation of Recreation Rights for Elderly Prisoners in Correctional Institutions: Tinjauan Yuridis Terhadap Pemenuhan Hak Rekreasi Bagi Narapidana Lansia Di Lembaga Pemasyarakatan - Farhan Fadlurrohman; Mitro Subroto (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2023)
The population of prisoners in correctional institutions is diverse including children, adults and the elderly. Elderly prisoners experience unique challenges. Elderly prisoners need special attention and treatment given their age and health condition. This research purposes to explore the implementation of recreational rights for elderly prisoners based on Undang-Undang Nomor 22 Tahun 2022 and to identify the impact of the implementation of recreational rights on the rehabilitation and prosperity of elderly prisoners in correctional institutions. The method used in this research can be described as normative research or literature study research, where the focus is on the analysis of library materials or secondary data. The results of the research found are that recreational activities provided to elderly prisoners can be in the form of outdoor physical activities, additional activities in the form of information and knowledge development of prisoners and daily entertainment activities. Although there are not many elderly prisoners, they need special attention according to their needs like children and women in Indonesia. Special treatment for elderly prisoners helps ease the process of rehabilitation and recovery